2022
DOI: 10.3847/1538-3881/ac68e7
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 34 Low-mass Comoving Systems Using NOIRLab Source Catalog DR2

Abstract: We present the discovery of 34 comoving systems containing an ultracool dwarf found by means of the NOIRLab Source Catalog (NSC) DR2. NSC’s angular resolution of ∼ 1″ allows for the detection of small separation binaries with significant proper motions. We used the catalog’s accurate proper motion measurements to identify the companions by cross-matching a previously compiled list of brown dwarf candidates with NSC DR2. The comoving pairs consist of either a very low-mass star and an ultracool companion, or a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 76 publications
0
8
0
Order By: Relevance
“…This could result from a limitation of the cloud-free Sonora Cholla models, as any clouds, or differences in the molecular absorption from the models, would significantly change the shape of the SED. While the source could be a binary brown dwarf system (see Burgasser et al 2003bBurgasser et al , 2006Cruz et al 2004;Dupuy et al 2015;Kiwy et al 2022;Calissendorff et al 2023, for examples in the literature), this may not significantly effect the observed colors.…”
Section: Jades-gs-bd-5mentioning
confidence: 99%
“…This could result from a limitation of the cloud-free Sonora Cholla models, as any clouds, or differences in the molecular absorption from the models, would significantly change the shape of the SED. While the source could be a binary brown dwarf system (see Burgasser et al 2003bBurgasser et al , 2006Cruz et al 2004;Dupuy et al 2015;Kiwy et al 2022;Calissendorff et al 2023, for examples in the literature), this may not significantly effect the observed colors.…”
Section: Jades-gs-bd-5mentioning
confidence: 99%
“…With these caveats in mind, we compared our systems with stellar binaries and exoplanetary systems from the literature. Stellar binaries are taken from El-Badry et al (2021), complemented with the list of low-mass systems compiled by Faherty et al (2020) and Kiwy et al (2022). Exoplanetary systems are taken from the NASA Exoplanet Archive.…”
Section: Sample Propertiesmentioning
confidence: 99%
“…Our initial list of candidates for the creation of this sample was the UltracoolSheet, 5 a public compilation of ultracool dwarfs (e.g., spectral types later than ∼M6) and directly imaged exoplanets compiled in Best et al (2020). To this list, we added several papers with spectroscopically classified L, T, or Y dwarfs that were either not included (Robert et al 2016;Kellogg et al 2017;Kuchner et al 2017;Pérez-Garrido et al 2017, 2018Schneider et al 2017;Greco et al 2019;Kiman et al 2019;Zhang et al 2019) or published after the creation of the UltracoolSheet in 2020 (Faherty et al 2020(Faherty et al , 2021Meisner et al 2020bMeisner et al , 2021Schneider et al 2020Schneider et al , 2022Zhang et al 2020;Marocco et al 2021;Kirkpatrick et al 2021;Kiwy et al 2022;Softich et al 2022;Vos et al 2022).…”
Section: Sample Selectionmentioning
confidence: 99%